4CPS-233 Therapeutic switch of antiretroviral treatments: efficacy, tolerability and reason for change. (23rd March 2022) - Meca, N; Pardo, J; Garreta, G; Sebastián, C; Iglesias, M; Salazar, F; Nicolás, J
Abstract : Background and importance: The introduction of bitherapy has been a great advance in antiretroviral treatment. This has made it possible to obtain the same results in terms of efficacy with a smaller number of active ingredients (API), simplification of dosage, reduction of adverse effects (AE) and decrease in interactions. Aim and objectives: Describe the patient's profile, description of current bitherapy and previous treatment The second objective was to study the efficacy, safety and interactions of bitherapy, as well as the reason for switching. Material and methods: A retrospective descriptive study conducted in a tertiary hospital. Patients treated with dolutegravir+lamivudine/dolutegravir+rilpivirine bitherapy during the period 2016–2021 were included. Variables were collected through the electronic medical record: demographics (sex, age), comorbidities, viral load (CV) and CD4 prior to change of therapy and 12 months post-switch, previous treatment and reason for change. Results: A total of 104 patients on treatment with 105 bitherapies based on dolutegravir/lamivudine (68/105) and dolutegravir/rilpivirine (37/105) were included. 70.2% were men with a median age of 51 (24–84) years. The main pretreatment for dolutegravir/lamivudine was dolutegravir/lamivudine/abacavir (79.4%), while for dolutegravir/rilpivirine it was dolutegravir/rilpivirine/tenofovir-alafenamide (78.4%). In 85.7% of patients it involved a reduction in the number of APIs (pre: 3 vs post: 2) and in 14.3% a simplification of the regimen to a single tablet/day. Prior to the switch, 97.1% of patients had undetectable CV (<50 copies/mL) and CD4 levels of 750 (300–2720) cells/µL. After 1 year post-switch, 95.2% were CV-negative with CD4 levels 800 (354–1580) cells/µL. One episode of nervousness was collected as an AE. No interactions were detected. The main reason for therapeutic switch was simplification (62.9%) followed by comorbidities, mainly cardiovascular (31.4%), AE (2.9%), interactions (1.9%) and loss of efficacy (0.9%). Conclusion and relevance: Treatment with dolutegravir-based bitherapies has proven to be an effective, safe therapy with no relevant interactions. The principal reason for switching to bitherapy is simplification, achieving a reduction in both the number of tablets and the number of APIs versus previous therapies. The role of the pharmacist was fundamental for pharmaceutical care and clinical follow-up, detection of interactions, as well as the monitoring of adverse effects. References and/or acknowledgements: Conflict of interest: No conflict of interest